PENGARUH PENYERTAAN MODAL PEMERINTAH DAERAH TERHADAP KINERJA KEUANGAN BANK ACEH - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2017)
This research aims to determine the effect of capital participation of local governments to increase the performance of PT Bank Aceh. Analysis of the data used in this research is multiple regression with the annual financial statements of banks viewed as evidence of the Bank Aceh financial performance’s period 2008-2014. In this research, descriptive analysis was conducted in order to obtain a clearer picture of the set of data obtained and analyzed in order to determine whether the independent variables in the form of the Government (PMP), Return on Assets (ROA) and Return on Equity (ROE) effect on the dependent variable is financial performance. The results showed that the variables PMP, ROA and ROE simultaneously affect financial performance. PMP partial variable effect on financial performance, RAO variables affect the financial performance, and ROE effect on financial performance. Suggestions in this study is the Regional to governments should give more equity to local companies in order to prosper and advance the company's financial performance from year to year.